6(x+4)-(x+3)=x+1

Simple and best practice solution for 6(x+4)-(x+3)=x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+4)-(x+3)=x+1 equation:


Simplifying
6(x + 4) + -1(x + 3) = x + 1

Reorder the terms:
6(4 + x) + -1(x + 3) = x + 1
(4 * 6 + x * 6) + -1(x + 3) = x + 1
(24 + 6x) + -1(x + 3) = x + 1

Reorder the terms:
24 + 6x + -1(3 + x) = x + 1
24 + 6x + (3 * -1 + x * -1) = x + 1
24 + 6x + (-3 + -1x) = x + 1

Reorder the terms:
24 + -3 + 6x + -1x = x + 1

Combine like terms: 24 + -3 = 21
21 + 6x + -1x = x + 1

Combine like terms: 6x + -1x = 5x
21 + 5x = x + 1

Reorder the terms:
21 + 5x = 1 + x

Solving
21 + 5x = 1 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
21 + 5x + -1x = 1 + x + -1x

Combine like terms: 5x + -1x = 4x
21 + 4x = 1 + x + -1x

Combine like terms: x + -1x = 0
21 + 4x = 1 + 0
21 + 4x = 1

Add '-21' to each side of the equation.
21 + -21 + 4x = 1 + -21

Combine like terms: 21 + -21 = 0
0 + 4x = 1 + -21
4x = 1 + -21

Combine like terms: 1 + -21 = -20
4x = -20

Divide each side by '4'.
x = -5

Simplifying
x = -5

See similar equations:

| 5xw+16x=0 | | -9=-x+10 | | -3+30=6 | | 60z^3+56z^2-32z=0 | | 14z^4-42z^3+6z^2= | | 4x*-86+x=40 | | 9+4x+7x=75 | | 6-(1+2k)=-(k-1) | | 53a-14=63a+32 | | 9=-x+10 | | 6n-9=39 | | 40=25+20m | | 8y-x=8 | | 3x+8=-3+4x | | =-15-8(9d-16) | | 8(a^2-49)=0 | | -4(5+k)=-(k-1) | | -7y^4(5y^2+6y-8)= | | 7v+7v=0 | | 6(3x-0.4)=9x-2.4 | | 8-6x=-4x+6 | | 0.5-(-x+3)=x-5 | | 15=-x+10 | | -7v+7v=0 | | 30=2k+14 | | 1.1x+4.7=0.6x+4.4 | | 6x+6=x+26 | | (-75)=y+4y+25 | | 17x+66+11x=-10+x | | 4g+3(-6+4g)=1-9 | | -5(11-2x)-3y=-6 | | 2z+33=17 |

Equations solver categories